(untitled) (International relations and international law Journal, 2022)
The new coronavirus at the end of 2019 is the common enemy of all mankind. The rapid spread of the COVID-19 pandemic poses a huge challenge to global public health security. At present, globalization goes far beyond economic activity and embraces the political, cultural, environmental and health security spheres. Deepening globalization has led to an unprecedented acceleration in the movement of goods and people across borders, and the growth of international trade and tourism in particular has made it extremely easy for infectious diseases to spread beyond individual countries and regions, resulting in widespread international transmission. Therefore, infectious diseases are no longer a matter of individual national or regional control, and sovereign states cannot respond to public health challenges with unilateral action alone. In the face of an increasingly serious global pandemic, there is broad consensus that the international community is working together to fight the pandemic. Fighting the pandemic is a double test of the ability of sovereign nations to govern and participate in global governance. Since the spread of the COVID-19 pandemic, China has taken the most comprehensive, rigorous, and meticulous measures to establish a “first line of defense” against the COVID-19 pandemic. Key words: Chinese model, pandemic, fighting the COVID-19, humanitarian aid.